Distributed swarming and stigmergic effects on ISIS networks: OODA Loop Model / Ahmad Shehabat and Teodor Mitew - Shehabat, Ahmad; Mitew, Teodor (Centre for Media and Information Warfare Studies, 2017)
The stigmergic swarming of digital media environments with propaganda and personal communication made the self-proclaimed Islamic State (also known as ISIS, IS, ISIL and Daesh) one of the strongest terror groups in the world. This study aims to identify the digital manoeuvre warfare tactics deployed by ISIS to survive the degrading operation initiated by its adversaries. In this paper, we emphasise that the information operations of terror organisations are not limited to a certain application or communication platform. Instead, the emergence of anonymous platforms (e.g., Justpase, Sendvid) and encryption communication applications (e.g., Telegram, WhatsApp) has enabled ISIS’s information operations and helped the organisation to maintain its networking structure. This paper examines the role played by anonymous platforms in ISIS’ operations from an information centric warfare perspective. The theoretical framework is derived from manoeuver warfare based on John Boyd’s OODA loop theory. The data collection involves a digital ethnography approach, concentrated on tracing and observing ISIS’ digital activities across anonymous platforms and encrypted communication channels. The study suggests that the failure of ISIS’ adversaries in operating inside the OODA loop of ISIS led to the organisation’s survival and proliferation of its information operations.